1997
DOI: 10.1016/s0375-9474(97)80701-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of kaon production at SIS energies

Abstract: We analyse the production and propagation of pions and kaons in heavy-ion reactions from 0.8 -1.8 A·GeV within a coupled channel transport approach including the kaon production channelsAssuming the hyperon selfenergy to be 2/3 of the nucleon selfenergy we find that all inclusive experimental K + spectra at SIS energies can be reproduced reasonably well without any selfenergies for the kaons although a slightly repulsive kaon potential cannot be excluded by the present data on kaon spectra and flow. : 25.75.+r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
154
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(174 citation statements)
references
References 50 publications
20
154
0
Order By: Relevance
“…This result is indeed compatible with the calculations using the free space total cross section of the π − + p → Λ + K 0 reaction, which provide an average total kaon production cross section of <K> = 71 µb for central Au + Au collisions at 2 AGeV. Note that the inclusion of even a slight modification of the K + mass because of the nuclear medium (without the corresponding changes introduced here) leads to a substantial reduction of the inclusive K + spectra (by as much as a factor of 2 or 3), compared to that calculated using the free space properties for the relevant hadrons [8].…”
Section: Impact On Heavy Ion Studiesmentioning
confidence: 92%
“…This result is indeed compatible with the calculations using the free space total cross section of the π − + p → Λ + K 0 reaction, which provide an average total kaon production cross section of <K> = 71 µb for central Au + Au collisions at 2 AGeV. Note that the inclusion of even a slight modification of the K + mass because of the nuclear medium (without the corresponding changes introduced here) leads to a substantial reduction of the inclusive K + spectra (by as much as a factor of 2 or 3), compared to that calculated using the free space properties for the relevant hadrons [8].…”
Section: Impact On Heavy Ion Studiesmentioning
confidence: 92%
“…For the energies considered, microscopic transport models are usually employed and have a history of succesfully describing experimental observables. Several previous works found that the production rates and properties of Kaons, for example are a promising probe to extract their medium interactions in low energy nuclear collisions [3,4,5,6,7,8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis of the out-of-plane [28,29] and sideward flow [19,30], the K + -nucleon potential is deduced to be mildly repulsive, and the measured K + production yields are in agreement with the scenario of a soft nuclear equation of state (incompressibility modulus K N ≈ 200 MeV) [31,32]. The interpretation of the K − data is still undergoing systematic evaluations to pin down the value of the presumed attractive K − -nucleon potential and its momentum dependence.…”
Section: Introductionmentioning
confidence: 99%